2017
DOI: 10.3389/fnagi.2017.00012
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Exosomes Spread and Cluster Around β-Amyloid Plaques in an Animal Model of Alzheimer’s Disease

Abstract: Exosomes, a type of extracellular vesicle, have been shown to be involved in many disorders, including Alzheimer’s disease (AD). Exosomes may contribute to the spread of misfolded proteins such as amyloid-β (Aβ) and α-synuclein. However, the specific diffusion process of exosomes and their final destination in brain are still unclear. In the present study, we isolated exosomes from peripheral plasma and injected them into the hippocampus of an AD mouse model, and investigated exosome diffusion. We found that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 64 publications
(106 reference statements)
1
61
0
Order By: Relevance
“…The study of exosomes in disease could provide important clues to the progression of neurodegenerative diseases and cancer. Previous studies provided evidence that amyloids involved in Alzheimer's disease, such as amyloid β, are released via exosomes and that exosome‐associated amyloids can act as seeds for plaque formation . Release of brain tumor vesicles and uptake by normal cells are associated with progression, angiogenesis, tumor cell invasion, and suppression of immune responses to the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The study of exosomes in disease could provide important clues to the progression of neurodegenerative diseases and cancer. Previous studies provided evidence that amyloids involved in Alzheimer's disease, such as amyloid β, are released via exosomes and that exosome‐associated amyloids can act as seeds for plaque formation . Release of brain tumor vesicles and uptake by normal cells are associated with progression, angiogenesis, tumor cell invasion, and suppression of immune responses to the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear localization of mutant Htt in astrocytes led us to investigate whether mHtt affects the transcription of molecules that are important for the release of exosomes. Previous studies show that ␣B-crystallin, which mediates exosome secretion (Gangalum et al, 2016), is decreased in HD mouse models, such as R6/2 and BACHD mice (Zabel et al, 2002;Oliveira et al, 2016). When comparing the expression of ␣B-crystallin in cultured astrocytes and neurons, we found that ␣B-crystallin is much more abundant in astrocytes (Fig.…”
Section: Mhtt Impairs ␣B-crystallin Expression Both In Cultured Astromentioning
confidence: 58%
“…Although ␣B-crystallin is decreased in HD mouse brains (Zabel et al, 2002;Oliveira et al, 2016), the mechanism underlying this decrease remains unknown. Because mRNA levels of ␣B-crystallin are reduced in HD KI astrocytes, we hypothesized that mHtt inhibits ␣B-crystallin transcription by affecting its promoter activity.…”
Section: Sp1 Mediates ␣B-crystallin Expression In Astrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein cargo derived from EVs isolated from AD patients has provided valued insight with respect to identifying potential ongoing pathological processes in the brains of individuals with preclinical and clinically diagnosed AD (Goetzl et al, ; Goetzl et al, ; Goetzl et al, ). In a mouse model of AD, serum‐derived EVs cluster around amyloid‐beta (Aβ) plaques and localize to microglia (Zheng et al, ). In this study, AD, but not normal ageing, was associated with a reduced capacity for microglia to internalize EVs.…”
Section: Novel Roles Of Mirnas As Intercellular Signaling Molecules Wmentioning
confidence: 99%